The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1590/s0102-053620160403
|View full text |Cite
|
Sign up to set email alerts
|

Baby leaf lettuce production in trays with reused and solarized substrate

Abstract: Concerning the baby leaf production in trays, substrate can be reused for a certain number of times depending on its chemical and physical characteristics, but populations of pathogens such as Pythium aphanidermatum and Rhizoctonia solani that can cause damping off of lettuce, can build up during the reuse of this substrate. Solar treatment in a solar collector can be an alternative for the disinfestation of these substrates. Thus, the objective of this research was to study the reuse of coconut fiber substrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…Cardoso et al (2010) observed a decrease in the percentage of aeration space and a consequent increase in water availability to melon plants cultivated in the reused substrate, but like the present study, productivity was not affected by reuse. Moraes et al (2016) and Purquerio et al (2016) also highlighted the advantage of reused coconut substrates over the first-use substrate in the lettuce baby leaf production without any productivity losses.…”
Section: Resultsmentioning
confidence: 99%
“…Cardoso et al (2010) observed a decrease in the percentage of aeration space and a consequent increase in water availability to melon plants cultivated in the reused substrate, but like the present study, productivity was not affected by reuse. Moraes et al (2016) and Purquerio et al (2016) also highlighted the advantage of reused coconut substrates over the first-use substrate in the lettuce baby leaf production without any productivity losses.…”
Section: Resultsmentioning
confidence: 99%
“…Esse substrato de origem vegetal natural, além de renovável é bastante leve. Oferta diversos benefícios como durabilidade extensa sem alteração de suas características físicas, ausência de patógenos, baixo custo para o produtor quando comparado a outros substratos e ainda a possibilidade de esterilização (MORAES et al, 2016).…”
Section: Fibra De Cocounclassified